Effect of freezing on physical properties of whey protein emulsion films - Soazo, Marina del Valle (2013)
The objective of this work was to study the effect of the freezing process on physical properties of whey protein emulsion films with different beeswax content dried at 5 ºC. Thickness, microstructure, water vapour permeability, solubility inwater, sorption isotherms and mechanical properties were measured in Control and Frozen films. The freezing process did not cause fractures or perforations in films, but films with beeswax showed a change in the appearance of the lipids after freezing. Only films with 40% of beeswax showed a significant increase in the water vapour permeability after freezing. The freezing process did not affect film solubility in water but produced small differences in the equilibrium moisture content values. In the puncture test, the freezing process increased puncture strength and deformation of films without beeswax but those parameters were not affected in films with beeswax. In tensile test, tensile strength and elastic modulus decreased, but elongation was not affected by freezing process. Principal component analysis accomplished an adequate condensation of the date grouping samples according to film formulation and treatment (Control and Frozen films). Indeed, the relationships of sample grouping and measured parameters were enlightened by principal component analysis. In conclusion, whey protein emulsion films were resistant to the freezing process (freezing, frozen storage and thawing) and could be a good alternative as a treatment to preserve the quality of frozen foods.